Recent Inventions and Trends in Algal Biofuels Research - Karemore, Ankush; Nayak, Manoranjan; Sen, Ramkrishna (Recent Patents on Biotechnology, 2016)
Background: In recent times, when energy crisis compounded by global warming and climate change is receiving worldwide attention, the emergence of algae, as a better feedstock for third-generation biofuels than energy crops or plants, holds great promise. As compared to conventional biofuels feedstocks, algae offer several advantages and can alone produce a significant amount of biofuels sustainably in a shorter period to fulfill the rising demand for energy. Objective: Towards commercialisation, there have been numerous efforts put for- ward for the development of algae-derived biofuel. This article reviews and summarizes the recent inventions and the current trends that are reported and captured in relevant patents pertaining to the novel methods of algae biomass cultivation and processing for biofuels and value-added products. In addition, the recent advancement in techniques and technologies for microalgal biofuel production has been highlighted. Methods: Various steps involved in the production of algal biofuels have been considered in this article. Moreover, the work that advances to improve the efficiency and cost-effectiveness of the processes for the manufacture of biofuels has been presented. Our survey was conducted in the patent databases: WIPO, Spacenet and USPTO. Results: There are still some technological bottlenecks that could be overcome by designing advanced photobioreactor and raceway ponds, developing new and low cost technologies for biomass cultivation, harvesting, drying and extraction. Conclusion: Recent advancement in algae biofuels methods is directed toward developing efficient and integrated systems to produce biofuels by overcoming the current challenges. However, further research effort is required to scale-up and improve the efficiency of these methods in the upstream and downstream technologies to make the cost of biofuels competitive with petroleum fuels.
Keywords: biofuels